Vizualizacija geometrijskih problemov na geoplošči - Cotič, Mara; Felda, Darjo; Mešinović, Sanela; Simčič, Blaž (Revija za elementarno izobraževanje, 2011)
Visualisation of Geometric Problems on Geoboard. Pupils’ understanding of geometry largely depends on their spatial perception, and teachers can help them by guiding them through five stages, described in details in our article. The first, i.e., the visual level is of extreme importance for pupils, since they learn about geometric concepts on a concrete, non-abstract level. In this regard, the Dutch didactic expert van Hiele suggests using various didactic materials. Geoboard is certainly one, being most frequently used for researching the basic geometrical concepts. In addition, pupils can solve geometrical problems by using geoboard, as well as discover and study facts which are new to them. Thus, we have visualised basic geometric concepts in our research, and developed problem-based instruction of geometry by using the geoboard, as well as showed that by using geoboard in geometry lessons, pupils can learn the basic geometric concepts properly, and develop problem-based approach to geometry. We have tested the adequacy of our model in an experiment on a sample of 113 pupils attending the seventh grade of elementary school. The results of our research shall be applicable above all in modernisation of geometry teaching in the third cycle of elementary school education and shall consequently contribute to pupils having better knowledge of geometry.
Keywords: geometry teaching and learning; geometry problems; visualisation; geoboard